2011
DOI: 10.1128/iai.00508-10
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of TH1, TH2, and TH17 Responses during Repeated Pulmonary Exposure toAspergillus fumigatusConidia

Abstract: Aspergillus fumigatus, a ubiquitous airborne fungus, can cause invasive infection in immunocompromised individuals but also triggers allergic bronchopulmonary aspergillosis in a subset of otherwise healthy individuals repeatedly exposed to the organism. This study addresses a critical gap in our understanding of the immunoregulation in response to repeated exposure to A. fumigatus conidia. C57BL/6 mice were challenged intranasally with A. fumigatus conidia weekly, and leukocyte composition, activation, and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 77 publications
(76 reference statements)
8
99
1
2
Order By: Relevance
“…[76][77][78] Although studies in mice found that a single exposure to A. fumagatis induced increases in Treg numbers and function in the lung, repeated exposure models, more akin to the exposure humans experience, was found to shift T-cell responses toward a pathogenic Th2-Th17 phenotype. 79 The secosteroid hormone 1,25-dihydroxyvitamin D3 (1,25[OH]D 3 ) has been shown in multiple disease states to induce Tregs. [80][81][82][83][84][85] However, patients with CRSwNP have reduced sinonasal levels of 1,25(OH)D 3 compared with controls or those with CRSsNP.…”
Section: Potential Causes Of Treg Dysfunctionmentioning
confidence: 99%
“…[76][77][78] Although studies in mice found that a single exposure to A. fumagatis induced increases in Treg numbers and function in the lung, repeated exposure models, more akin to the exposure humans experience, was found to shift T-cell responses toward a pathogenic Th2-Th17 phenotype. 79 The secosteroid hormone 1,25-dihydroxyvitamin D3 (1,25[OH]D 3 ) has been shown in multiple disease states to induce Tregs. [80][81][82][83][84][85] However, patients with CRSwNP have reduced sinonasal levels of 1,25(OH)D 3 compared with controls or those with CRSsNP.…”
Section: Potential Causes Of Treg Dysfunctionmentioning
confidence: 99%
“…IL-6 also promotes inflammation and pulmonary fibrosis, 41,56 suggesting that the 'Th2 theory' is probably inadequate to explain the diverse forms of asthma in humans and the various inflammatory responses observed in animal models of allergic asthma. 12,57,58 In recent years, a number of research groups have demonstrated a more direct role for IL-17 in exacerbating eosinophilia and neutrophilia. 12,[58][59][60] Similarly, the neutralization of IL-6 has been associated with decreased inflammation in allergic mice, and this phenomenon occurs in conjunction with IL-17A, indicating that IL-6 regulates IL-17A production in models of lung injury.…”
Section: Fungal Conidia Inhalation Significantly Increases Collagen Dmentioning
confidence: 99%
“…12,57,58 In recent years, a number of research groups have demonstrated a more direct role for IL-17 in exacerbating eosinophilia and neutrophilia. 12,[58][59][60] Similarly, the neutralization of IL-6 has been associated with decreased inflammation in allergic mice, and this phenomenon occurs in conjunction with IL-17A, indicating that IL-6 regulates IL-17A production in models of lung injury. 41 Consistent with these observations, we also observed an increased IL-17 and IL-6 response in the absence of B lymphocytes in J H 2/2 mice.…”
Section: Fungal Conidia Inhalation Significantly Increases Collagen Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Th1, Th2, and Th17 responses in mice were shown to evolve during repeated pulmonary exposure to Aspergillus (Murdock et al, 2011). Treg cells involved in the development of aspergillosis provide the host with adequate defense without necessarily eliminating the fungus or causing unacceptable levels of host damage (Montagnoli et al, 2006).…”
Section: Introductionmentioning
confidence: 99%